Data for iTRAQ profiling of micro-vesicular plasma specimens : in search of potential prognostic circulatory biomarkers for Lacunar infarction - Datta, Arnab (2018)
To discover potential prognostic biomarkers of Lacunar infarction (LACI), here we present quantitative proteomics data of plasma microvesicle-enriched fraction derived by comparative isobaric profiling of three groups of prospectively followed-up LACI patients (LACI – no adverse outcome, LACI –recurrent vascular event and LACI – cognitive decline) and a demographically matched control group. We confidently (unused prot score >3, FDR=1.1%) identified 183 proteins, 43 out of which were significantly regulated (p-value<0.05) in at least one of the three LACI groups in comparison to control group. Bioinformatics analysis and data mining revealed upregulation of brain-specific proteins including myelin basic protein, proteins of coagulation cascade (e.g., fibrinogen alpha chain, fibrinogen beta chain) and focal adhesion (e.g., integrin alpha-IIb, talin-1, and filamin-A) while albumin was downregulated in both groups of patients with adverse outcome. The data of this study are also in line with our previously published article entitled “Discovery of prognostic biomarker candidates of Lacunar infarction by quantitative proteomics of microvesicles enriched plasma” by Datta et al. (2014). The raw data had been deposited to the ProteomeXchange consortium with identifier PXD000748.